Covid-19: Digital Signature Impact on Higher Education Motivation Performance - Untung Rahardja; Sudaryono Sudaryono; Nuke Puji Lestari Santoso; Adam Faturahman; Qurotul Aini (STMIK Dharma Wacana, 2020)
At present, the process of validating documents for certain purposes cannot be done face-to-face because of the Covid-19 pandemic. Therefore, this research aims to maximize the existence of smart digital signature technology that guarantees its safety and validity without having to meet face to face. Encrypted digital signatures with RSA-SHA256 with cloud storage features that can share documents. The waterfall method for building systems, the collection of data generated for analysis by observation, and online questionnaires using Google Form.Â Based on the characteristics of the system, the satisfaction factor analysis of the system with the Slovin formula processed by the SUS score resulted in a score of 95 > 70. The final result of this study is that the digital signature system has a significant impact on increasing motivation to facilitate authorization and secure documents.